2018
DOI: 10.3390/foods7030028
|View full text |Cite
|
Sign up to set email alerts
|

Protein Bread Fortification with Cumin and Caraway Seeds and By-Product Flour

Abstract: Malnutrition continues to be a key health problem in developing regions. The valorization of food waste appears as an ideal way to prevent malnutrition and improve people’s access to food. Cumin (Cuminum cyminum L.) and caraway (Carum carvi L.) oilseeds are commonly used for cuisine and medicinal purposes. However, remaining cakes after oil extraction are usually underutilized. In order to assess the usefulness of these by-products in food applications, this study investigated the effect of their addition to p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 18 publications
3
11
0
Order By: Relevance
“…Moreover, it was reported that residual cakes, after oil extraction, are considered to be a good source of natural antioxidants [ 37 ]. It has also been found that bread fortification with pseudo-cereals increased the antioxidant potential of obtained bread, which is in line with our results [ 38 , 39 ]. El-Demery et al (2015), obtained higher antioxidant activity in bread fortified with full fat flaxseed than that fortified with defatted flaxseed [ 20 ].…”
Section: Resultssupporting
confidence: 93%
“…Moreover, it was reported that residual cakes, after oil extraction, are considered to be a good source of natural antioxidants [ 37 ]. It has also been found that bread fortification with pseudo-cereals increased the antioxidant potential of obtained bread, which is in line with our results [ 38 , 39 ]. El-Demery et al (2015), obtained higher antioxidant activity in bread fortified with full fat flaxseed than that fortified with defatted flaxseed [ 20 ].…”
Section: Resultssupporting
confidence: 93%
“…The energy value obtained in SFP-enriched breads was higher ( p < 0.05) than the control bread and this may be related to the higher lipid content of the breads. A similar result has been obtained previously by researchers fortifying bread with cumin and caraway flour [27].…”
Section: Resultssupporting
confidence: 90%
“…Consumption of food with phenolic-rich ingredients is highly recommended due to their health-promoting effects as they are involved in the prevention of many diseases such as cancers, diabetes, and cardiovascular diseases [27]. SFP bread had lower TPC values than the control bread (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Sayed‐Ahmad et al () showed that bread fortification with fennel cake and seed had beneficial effects on the phenolic concentration, the antioxidant activity, and the quality of the protein. Sayed‐Ahmad et al () also showed the positive impact of bread fortification with different levels of cumin and caraway seeds, and by‐products on the bread protein quality and overall acceptance. This fortification was advantageous due to the increased nutritional value and higher moisture content while maintaining acceptable rheological and sensory properties.…”
Section: Introductionmentioning
confidence: 94%